Method for evaluating flow conductivity of quartz sand proppant under different particle size combinations

By fracturing and permeability testing of quartz sand proppant, the sample-permeability curve was established, and the problem of cumbersome and inaccurate measurement of the flow diversion capacity of quartz sand proppant in the prior art was solved, and efficient and accurate evaluation of the flow diversion capacity was achieved.

CN119510248AActive Publication Date: 2025-02-25WUHAN UNIV OF TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411513235.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-25
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

In the prior art, the quartz sand proppant flow diversion capacity measurement method has problems such as cumbersome steps, long time, many quality of samples required to be tested, and the laboratory test results are not closely integrated with actual production.

Method used

By providing shale rock samples and quartz sand proppant samples with different particle size combinations, fracturing and permeability tests were performed, sample-permeability curves were established, and the flow-guiding ability of quartz sand proppant with different particle size combinations was evaluated.

Benefits of technology

This method simplifies the flow diversion capacity measurement process, improves measurement efficiency and accuracy, makes the experimental results closer to actual production conditions, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510248A_ABST
    Figure CN119510248A_ABST
Patent Text Reader

Abstract

The invention discloses a flow conductivity evaluation method for a quartz sand proppant under different particle size combinations, and belongs to the technical field of unconventional oil and gas fracturing exploitation. The method comprises the following steps: respectively providing a shale rock sample and quartz sand proppant samples with different particle size combinations; fracturing the shale rock sample to obtain a shale rock sample with cracks, and then testing the permeability to obtain the permeability of the shale rock sample with cracks; respectively embedding quartz sand proppant samples with different particle size combinations into the shale rock sample with the cracks, and then testing the permeability to respectively obtain the permeability of the quartz sand proppant samples embedded with different particle size combinations; and establishing a sample-permeability curve according to the permeability result of the sample, and evaluating the flow conductivity of the quartz sand proppant with different particle size combinations according to the permeability in the curve. The whole evaluation method is simple, efficient and convenient for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of unconventional oil and gas fracturing and exploitation, and in particular relates to a method for evaluating the conductivity of quartz sand proppants under different particle size combinations. Background Art

[0002] In the process of hydraulic fracturing of oil and gas resources, proppant is one of the important factors affecting the benefits of mining. The higher the proppant conductivity, the better the migration effect of oil and gas resources in the fracturing cracks. The factors affecting the proppant conductivity include particle size, crushing rate, acid solubility and porosity, among which particle size is the main influencing factor. Proppant with appropriate particle size is not only the minimum requirement for hydraulic fracturing, but also a higher standard pursued by oil companies for benefits. Unlike conventional oil and gas resources, hydraulic fracturing of shale reservoir oil and gas resources requires proppant with equivalent particle size and higher strength.

[0003] At present, in the process of hydraulic fracturing of oil and gas resources, at least two proppants with different particle sizes are combined to improve the extraction efficiency. Regarding the determination of the conductivity of the combined proppants, the traditional method is to use the industry standard SYT6302-2019 "Test Method for Conductivity of Fracturing Proppants" for testing.

[0004] However, the testing methods in the prior art have technical problems such as complicated steps, long time consumption, large amount of sample mass required for testing, and the lack of close integration between laboratory test results and actual production. Summary of the invention

[0005] The purpose of the present invention is to provide a method for evaluating the conductivity of quartz sand proppants with different particle size combinations, so as to solve the technical problems of the existing proppant conductivity measurement methods, such as complicated steps, long time consumption, large amount of sample mass required for testing, and the lack of close integration between laboratory test results and actual production.

[0006] In a first aspect, the present invention provides a method for evaluating the conductivity of quartz sand proppants with different particle size combinations, comprising the following steps: providing a shale rock sample and quartz sand proppant samples with different particle size combinations, respectively; fracturing the shale rock sample to obtain a shale rock sample with cracks, and then performing a permeability test to obtain the permeability of the shale rock sample with cracks; embedding the quartz sand proppant samples with different particle size combinations into the shale rock samples with cracks, respectively, and then performing a permeability test to respectively obtain the permeabilities of the quartz sand proppant samples embedded with different particle size combinations; establishing a sample-permeability curve based on the permeability results of the sample, and evaluating the conductivity of the quartz sand proppants with different particle size combinations based on the permeability in the curve.

[0007] In the present invention, the inventors have discovered that the use of fracturing technology to create fractures can simulate natural fractures of oil wells hydraulically fractured under formation pressure at a certain depth, solving the technical problem that the test results of traditional laboratory tests are not closely integrated with actual production, making the experimental results more accurate and reliable; in addition, according to Darcy's law, the present invention only needs to test the permeability of quartz sand proppant samples with different particle size combinations to obtain the size of the conductivity of quartz sand proppant samples with different particle size combinations, and the entire evaluation method is simple and efficient, and is convenient for large-scale application.

[0008] In some embodiments, the shale rock sample includes a shale core column.

[0009] In some embodiments, the silica sand proppant samples of different particle size combinations include silica sand proppant samples of 30 / 50 mesh, 40 / 70 mesh, 60 / 120 mesh, 70 / 140 mesh, and 100 / 200 mesh combinations.

[0010] In the present invention, quartz sand proppant samples with other different particle size combinations can also be selected according to actual test needs. In the present invention, quartz sand proppant samples with 30 / 50 mesh, 40 / 70 mesh, 60 / 120 mesh, 70 / 140 mesh and 100 / 200 mesh combinations are preferred.

[0011] In some embodiments, the quartz sand proppant samples with different particle size combinations are obtained by combining quartz sand after scrubbing, grinding, and screening according to the method in the industry standard SY / T 5108-2014 "Proppant Performance Test Method for Hydraulic Fracturing and Gravel Packing Operations".

[0012] In some embodiments, during the permeability test of a shale rock sample with cracks, before the shale rock sample is fractured, a step of drying the fractured shale rock sample is also included; wherein the drying step specifically includes: drying for 24 to 48 hours, for example, 24 hours, 28 hours, 32 hours, 36 hours, 40 hours, 44 hours, 48 ​​hours or other values ​​within the range, at a temperature of 60 to 80°C (for example, 60°C, 65°C, 70°C, 75°C, 80°C or other values ​​within the range).

[0013] In some embodiments, during the permeability testing of a shale rock sample with cracks, fracturing specifically includes: using a rock triaxial system (PDP-200) for fracturing to obtain a shale rock sample with cracks; wherein the cracks are natural cracks hydraulically fractured under formation pressure simulating an oil well depth of 1800 to 2200 m (for example, 1800 m, 1900 m, 2000 m, 2100 m, 2200 m or other values ​​within this range).

[0014] In the present invention, by using the rock triaxial system for fracturing and creating fractures, it is possible to simulate the hydraulic fracturing of natural fractures in an oil well under formation pressure at a certain depth. When further quartz sand proppant samples with different particle size combinations are embedded in the natural fractures for testing, the conductivity of the quartz sand proppant samples with different particle size combinations in actual application can be reflected.

[0015] In some embodiments, the permeability test specifically includes: using a pressure porosity permeability tester to perform a test at a pressure of 18-22 MPa (eg, 18 MPa, 19 MPa, 20 MPa, 21 MPa, 22 MPa or other values ​​within the range).

[0016] In the present invention, when the overburden porosity and permeability tester is used for testing, the method has the advantages of simple method and high accuracy.

[0017] In some embodiments, during the permeability test of quartz sand proppant samples embedded with different particle size combinations, before the quartz sand proppant samples with different particle size combinations are respectively embedded in shale rock samples with fractures, the step of drying the quartz sand proppant samples with different particle size combinations is also included; wherein the drying step specifically includes: drying for 24 to 48 hours, for example, 24 hours, 28 hours, 32 hours, 36 hours, 40 hours, 44 hours, 48 ​​hours or other values ​​within the range, at a temperature of 60 to 80°C (for example, 60°C, 65°C, 70°C, 75°C, 80°C or other values ​​within the range).

[0018] In some embodiments, during the permeability test of quartz sand proppant samples embedded with different particle size combinations, the permeability test specifically includes: using an overburden porosity permeability tester to perform a test at a pressure of 18 to 22 MPa (for example, 18 MPa, 19 MPa, 20 MPa, 21 MPa, 22 MPa or other values ​​within this range).

[0019] In some embodiments, in evaluating the conductivity of silica sand proppants of different particle size combinations, the conductivity is proportional to the permeability.

[0020] In the present invention, according to Darcy's law, the conductivity is proportional to the permeability. Therefore, by simply testing the permeability of quartz sand proppants with different particle size combinations, the conductivity of quartz sand proppants with different particle size combinations can be quickly, simply and efficiently obtained.

[0021] The beneficial effects of the present invention are as follows: different from the prior art, the present invention uses fracturing technology to create fractures, which can simulate the natural fractures of oil wells hydraulically fractured under formation pressure at a certain depth, and solves the technical problem that the test results of quartz sand proppants tested in traditional laboratories are not closely combined with actual production, making the experimental results more accurate and reliable; in addition, according to Darcy's law, the present invention only needs to test the permeability of quartz sand proppant samples with different particle size combinations to obtain the size of the conductivity of quartz sand proppant samples with different particle size combinations, and the entire evaluation method is simple and efficient, and is convenient for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a flow chart of the method for evaluating the conductivity of quartz sand proppants with different particle size combinations in the present invention; Figure 2 It is a schematic diagram of the structure of the shale core column sample after fracturing in the present invention; Figure 3 It is a schematic diagram of the structure of the quartz sand proppant embedded in the shale core column after fracturing in the present invention; Figure 4 The sample-permeability curve diagram of the shale rock sample with fractures and the quartz sand proppant sample embedded with different particle size combinations in the present invention; In the figure, the meanings of the reference numerals are as follows: 1: shale core column; 2: natural fracture; 3: quartz sand proppant. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified.

[0025] See also Figure 1, which is a flow chart of the method for evaluating the conductivity of quartz sand proppants under different particle size combinations in the present invention. Specifically, the method includes the following steps: providing shale rock samples and quartz sand proppant samples with different particle size combinations respectively; fracturing the shale rock samples to obtain shale rock samples with cracks, and then performing a permeability test to obtain the permeability of the shale rock samples with cracks; embedding the quartz sand proppant samples with different particle size combinations into the shale rock samples with cracks respectively, and then performing a permeability test to obtain the permeabilities of the quartz sand proppant samples embedded with different particle size combinations respectively; establishing a sample-permeability curve based on the permeability results of the samples, and evaluating the conductivity of the quartz sand proppants with different particle size combinations based on the permeability in the curve.

[0026] Please continue reading Figure 2 and 3 ,in, Figure 2 It is a schematic diagram of the structure of a shale core column 1 sample after fracturing in the present invention. After fracturing, the shale core column 1 obtains a natural fracture 2. Figure 3 It is a schematic diagram of the structure of the quartz sand proppant 3 embedded in the shale core column 1 after fracturing in the present invention.

[0027] Example 1 A method for evaluating the conductivity of quartz sand proppants with different particle size combinations comprises the following steps: S1. Provide shale rock samples and quartz sand proppant samples with different particle size combinations respectively; S2, fracturing the shale rock sample to obtain a shale rock sample with cracks, and then performing a permeability test to obtain the permeability of the shale rock sample with cracks; S3, respectively embedding the quartz sand proppant samples with different particle size combinations into the shale rock samples with fractures, and then performing a permeability test to obtain the permeabilities of the quartz sand proppant samples embedded with different particle size combinations; S4. According to the permeability results of the samples, a sample-permeability curve is established, and according to the permeability in the curve, the conductivity of the quartz sand proppant with different particle size combinations is evaluated.

[0028] Exemplarily, the conductivity of silica sand proppant samples of 30 / 50 mesh, 40 / 70 mesh, 60 / 120 mesh, 70 / 140 mesh, and 100 / 200 mesh combinations was evaluated.

[0029] Specifically, the steps include: S1. Select a shale core column 1 sample, scrub, grind and screen the quartz sand, and then combine it according to the method in the industry standard SY / T5108-2014 "Test Method for Proppant Performance for Hydraulic Fracturing and Gravel Packing Operations" to obtain quartz sand proppant samples of 30 / 50 mesh, 40 / 70 mesh, 60 / 120 mesh, 70 / 140 mesh and 100 / 200 mesh combinations; S2, drying the shale core column 1 sample in step S1 at a temperature of 70° C. for 36 hours, and then fracturing it using a rock triaxial system to obtain a shale rock sample with natural fractures 2 of hydraulic fracturing under a formation pressure simulating an oil well depth of 2000 m, and then using an overburden porosity and permeability tester to perform a permeability test at a pressure of 20 MPa to obtain the permeability of the shale rock sample; S3, drying the 30 / 50 mesh quartz sand proppant sample in step S1 at a temperature of 70°C for 36 hours, and then embedding it into the natural crack 2 of the shale rock sample in step S2, using an overburden porosity permeability tester, at a pressure of 20MPa, to obtain the permeability of the embedded 30 / 50 mesh quartz sand proppant sample; taking out the 30 / 50 mesh quartz sand proppant sample from the natural crack 2 of the shale rock sample, and then at a temperature of 70°C, The shale rock sample is dried for 36 hours, and the quartz sand proppant sample of 40 / 70 mesh combination in step S1 is continuously embedded into the natural fracture 2 of the dried shale rock sample. The permeability of the quartz sand proppant sample embedded in the 40 / 70 mesh combination is measured by the above method; similarly, the permeability of the quartz sand proppant sample embedded in the 60 / 120 mesh combination, the permeability of the quartz sand proppant sample embedded in the 70 / 140 mesh combination, and the permeability of the quartz sand proppant sample embedded in the 100 / 200 mesh combination are respectively obtained; The permeability results of the samples in steps S2 and S3 are shown in Table 1 below: Table 1 Permeability results of samples (test repeated 3 times)

[0030] S4. According to the permeability results of the samples in steps S2 and S3, a sample-permeability curve (such as Figure 4 The conductivity of quartz sand proppants with different particle size combinations was evaluated based on the permeability in the curve.

[0031] from Figure 4It can be seen that compared with the rock sample with only cracks, the rock sample embedded with quartz sand proppants has a higher permeability. As the particle size of the proppant in the embedded rock sample increases, the permeability increases. When the particle size of the embedded proppant is 70 / 140 mesh, the permeability change tends to be stable. Furthermore, according to Darcy's law, the conductivity of quartz sand proppants is proportional to the permeability. Therefore, the permeability of quartz sand proppants with different particle size combinations can be used to determine the conductivity of quartz sand proppants with different particle size combinations.

[0032] Further, from Figure 4 It can be seen that the quartz sand proppant with a combination of 30 / 50 mesh has the highest permeability and the strongest conductivity. However, when the quartz sand proppant is used in the actual shale reservoir oil and gas resource exploitation, the particle size of the quartz sand proppant must be considered under the premise of ensuring a high permeability. Generally, the smaller the particle size, the better. Therefore, the quartz sand proppant with a combination of 70 / 140 mesh selected in the present invention has the best effect when used in the actual shale reservoir oil and gas resource exploitation.

[0033] In summary, the present invention only needs to test the permeability of quartz sand proppant samples with different particle size combinations to obtain the size of the conductivity of quartz sand proppant samples with different particle size combinations, and the entire evaluation method is simple, efficient, and convenient for large-scale application.

[0034] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.

[0035] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for evaluating the conductivity of quartz sand proppants with different particle size combinations, characterized in that: The steps include: Provide shale rock samples and quartz sand proppant samples with different particle size combinations; Fracturing the shale rock sample to obtain a shale rock sample with cracks, and then performing a permeability test to obtain the permeability of the shale rock sample with cracks; The quartz sand proppant samples with different particle size combinations are respectively embedded in the shale rock samples with fractures, and then a permeability test is performed to obtain the permeabilities of the quartz sand proppant samples embedded with different particle size combinations; According to the permeability results of the samples, a sample-permeability curve is established, and according to the permeability in the curve, the conductivity of quartz sand proppants with different particle size combinations is evaluated.

2. The method for evaluating the conductivity of quartz sand proppants with different particle size combinations according to claim 1, characterized in that: The shale rock sample includes a shale core column.

3. The method for evaluating the conductivity of quartz sand proppants with different particle size combinations according to claim 1, characterized in that: The quartz sand proppant samples with different particle size combinations include quartz sand proppant samples with 30 / 50 mesh, 40 / 70 mesh, 60 / 120 mesh, 70 / 140 mesh and 100 / 200 mesh combinations.

4. The method for evaluating the conductivity of quartz sand proppants with different particle size combinations according to claim 1, characterized in that: The quartz sand proppant samples with different particle size combinations are obtained by combining quartz sand after scrubbing, grinding and screening according to the method in the industry standard SY / T 5108-2014 "Proppant Performance Test Method for Hydraulic Fracturing and Gravel Packing Operations".

5. The method for evaluating the conductivity of quartz sand proppants with different particle size combinations according to claim 1, characterized in that: In the process of testing the permeability of the shale rock sample with cracks, before fracturing the shale rock sample, the method further includes the step of drying the fracturing shale rock sample; The drying step specifically includes: drying at a temperature of 60-80° C. for 24-48 hours.

6. The method for evaluating the conductivity of quartz sand proppants with different particle size combinations according to claim 1, characterized in that: In the test process of the permeability of the shale rock sample with cracks, the fracturing specifically includes: using a rock triaxial system to fracture to obtain a shale rock sample with cracks; The cracks are natural cracks simulated by hydraulic fracturing under formation pressure at a depth of 1800 to 2200 m in an oil well.

7. The method for evaluating the conductivity of quartz sand proppants with different particle size combinations according to claim 1, characterized in that: The permeability test specifically includes: using a covered pressure porosity permeability tester to conduct the test at a pressure of 18~22MPa.

8. The method for evaluating the conductivity of quartz sand proppants with different particle size combinations according to claim 1, characterized in that: In the test process of the permeability of the quartz sand proppant samples embedded with different particle size combinations, before the quartz sand proppant samples with different particle size combinations are respectively embedded in the shale rock samples with fractures, the step of drying the quartz sand proppant samples with different particle size combinations is also included; The drying step specifically includes: drying at a temperature of 60-80° C. for 24-48 hours.

9. The method for evaluating the conductivity of quartz sand proppants with different particle size combinations according to claim 1, characterized in that: In the permeability test process of the quartz sand proppant samples embedded with different particle size combinations, the permeability test specifically includes: using an overburden porosity permeability tester to perform the test at a pressure of 18-22 MPa.

10. The method for evaluating the conductivity of quartz sand proppants with different particle size combinations according to claim 1, characterized in that: In the process of evaluating the flow conductivity of the quartz sand proppants with different particle size combinations, the flow conductivity is proportional to the permeability.

Citation Information

Patent Citations

  • Method applied to evaluation of flow conductivity of shale-gas-combined sand fracturing fracture

    CN104358554A

  • Hydro-fracture propping agent parameter optimization method

    CN107085638A

  • Multi-lithology fracturing crack test method

    CN113218770A

  • Fracture conductivity prediction method based on multi-particle-size proppant accumulation body

    CN118153469A

  • Method for testing a proppant

    US10281380B1